Spectroscopic Studies of the Magnetic Excitation and Spin‐Phonon Couplings in a Single‐Molecule Magnet. Issue 69 (14th November 2019) - Stavretis, Shelby E.; Moseley, Duncan H.; Fei, Fan; Cui, Hui‐Hui; Cheng, Yongqiang; Podlesnyak, Andrey A.; Wang, Xiaoping; Daemen, Luke L.; Hoffmann, Christina M.; Ozerov, Mykhaylo; Lu, Zhengguang; Thirunavukkuarasu, Komalavalli; et al.
Abstract: Large separations between ground and excited magnetic states in single‐molecule magnets (SMMs) are desirable to reduce the likelihood of spin reversal in the molecules. Spin‐phonon coupling is a process leading to magnetic relaxation. Both the reversal and coupling, making SMMs lose magnetic moments, are undesirable. However, direct determination of large magnetic states separations (>45 cm −1 ) is challenging, and few detailed investigations of the spin‐phonon coupling have been conducted. The magnetic separation in [Co(12‐crown‐4)2 ](I3 )2 (12‐crown‐4) (1 ) is determined and its spin‐phonon coupling is probed by inelastic neutron scattering (INS) and far‐IR spectroscopy. INS, using oriented single crystals, shows a magnetic transition at 49.4(1.0) cm −1 . Far‐IR reveals that the magnetic transition and nearby phonons are coupled, a rarely observed phenomenon, with spin‐phonon coupling constants of 1.7–2.5 cm −1 . The current work spectroscopically determines the ground–excited magnetic states separation in an SMM and quantifies its spin‐phonon coupling, shedding light on the process causing magnetic relaxation. Abstract : In a spin : Inelastic neutron scattering (INS) and far‐IR studies lead to the observation of the magnetic transition and rarely reported spin‐phonon coupling in a Co II single‐molecule magnet (SMM).